(untitled) (PERcursos Linguísticos, 2022)
The objective of this article is to make reflections of a theoretical nature on the gramatical status of attributive clauses (HALLIDAY; MATTHIESSEN, 2014). For this, the text takes up results obtained by Santana (2021) with regard to the description of this type of clause. The problem found refers to the difficulty in explaining the selection of the participants of the clause as a function of the process, as well as in describing the selection of participant role coded by these constituents based on the semantics of the verb. The hypothesis is that the constituents of these clauses are a function of the construction, and not of the centrality of the predicator. In support of the explanation, the selection of 91 intensive clauses collected was carried out. Aspects of these constructions not described by the researcher in the previous investigation were observed, such as: the nature of the coding constituents of the Carrier participant, the frequency of occurrence of verbal forms, the relationship of these forms with the qualification and classification networks. The text concludes by proposing a change of perspective for the treatment of relational constructions. This change may enable answers to open questions regarding the nature of these constructions.